Microneedle-based sustained release delivery of TNF-α/IL-6R dual-specific fenobody alleviates inflammation and promotes bone regeneration in rheumatoid arthritis rat model - Xiqian Zhang; Jian Chen; Na Huang; Qi Chen; Muhammad Asad Farooq; Ping Ouyang; Kaisong Huang; Kangsheng Liao; Wanjun He; Kai Cui; Dan Jiang; Guangxian Xu (Materials Today Bio)
Rheumatoid arthritis (RA) is a chronic, systemic autoimmune disease characterized by inflammatory imbalance. The cytokine-targeted therapy is a non-traditional form of RA treatment that is mighty effective but poses the challenge of pharmaceutical storage conditions, professional injection, frequent injection administrations and poor patient adherence, and due to individual differences in sensitivity to TNF-α and IL-6R, monotherapy with a single antibody is effective in fewer than 30 % of cases. Hence, to address these issues, we have developed a macromolecule polymer GelMA microneedle sustained-release platform for transdermal delivery of a dual-specific fenobody targeting TNF-α and IL-6R in an arthritic rat model. The results demonstrated that the IL-6R-TNF-α-fenobody exhibited enhanced specificity and affinity and an extended half-life. IL-6R-TNF-α-fenobody effectively neutralizes rhTNF-α-induced cytotoxicity in L929 cells, while inhibiting the phosphorylation of IκBα and p65 in the classical NF-κB signaling pathway, and significantly blocks JAK-dependent phosphorylation of STAT3, thereby exerting its anti-inflammatory effects via multiple signaling pathways. The GelMA hydrogel microneedle sustained-release platform facilitates controlled cargo delivery to alleviate the inflammatory environment and reduce over-activated synoviocyte activity, thus promoting bone and joint regeneration. In collagen-induced arthritis (CIA) rats, cross-linked gelatin microneedles demonstrated high mechanical strength, facilitating the effective delivery of fenobodies to the dermis for optimal microcirculation, reduced levels of inflammatory factors, this strategy significantly inhibited the progression of RA. Overall, the IL-6R-TNF-α-Fenobody therapy promoted bone and joint regeneration by synergistic inflammation-resolving, osteogenesis. Excitingly, the microneedle group showed comparable treatment outcomes to the injection group, providing a portable, painless, sustained-release alternative that could enhance patient compliance by reducing the need for frequent professional injections.